Catheter-related blood stream infection caused by Dermacoccus barathri, representing the first case of Dermacoccus infection in humans. Issue 8 (August 2015) - Takahashi, Nobuhiro; Shinjoh, Masayoshi; Tomita, Hirofumi; Fujino, Akihiro; Sugita, Kayoko; Katohno, Yasuhiro; Kuroda, Tatsuo; Kikuchi, Ken
Abstract A 7-year-old boy undergoing home parenteral nutrition with totally implantable central venous access device for chronic intestinal pseudo-obstruction experienced repeated episodes of fever with a temperature above 39.0 °C despite the antibiotic treatment. The fever was considered to be catheter-related blood stream infections, as no other etiology could be justified. Repeated blood culture tests revealed negative after 1-week incubation, whereas some samples of blood collected from the central venous catheter yielded positive and gram-positive rods were detected. These bacteria were detected repeatedly, then the central venous access device was removed with consideration for the possibility of this bacteria being a pathogen. Thereafter, the fever did not recur and the blood culture tests were negative. The causative agent was identified as Dermacoccus barathri based on the 16S rRNA gene sequence and phylogenetic analysis of 6118-bp concatenated sequences of 4 housekeeping genes. Genus Dermacoccus are one form of Actinomycetes isolated from human skin and water, but human infection with Dermacoccus spp. has not been previously reported and the pathogenicity of the bacteria remains unclear. To our knowledge, this is the first reported case of Dermacoccus infection in humans.